Analisis Pengaruh Penggunaan e-wallet Terhadap Pola Konsumsi Mahasiswa Universitas Negeri Medan di Era Digital: Penelitian - Alexa Angelica Nababan; Wiliam Barker Hutabarat; Rouli Pranatalia Simanjuntak; M Yudi Fajri (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The rapid development of digital technology, particularly electronic wallets (e-wallets), has significantly transformed students’ consumption patterns. This study aims to analyze the influence of e-wallet usage on the consumption behavior of Universitas Negeri Medan students in the digital era. The main focus is to examine how usage intensity, ease of access, and promotional offers contribute to students’ consumptive tendencies. This research employs a qualitative phenomenological approach with a snowball sampling technique involving ten informants, complemented by descriptive data from one hundred survey respondents to strengthen field findings. Data were collected through in-depth interviews, observation, and transaction record analysis. The results reveal that most students use e-wallets (GoPay, OVO, DANA, ShopeePay, LinkAja) due to convenience, speed, and promotional incentives. The findings further indicate that e-wallet usage increases transaction frequency, triggers impulsive consumption behavior, and shifts spending from primary needs to lifestyle-oriented expenses. Although e-wallets provide efficiency in financial transactions, the lack of financial literacy makes students vulnerable to overspending. The study concludes that e-wallets are not the root cause of consumptive behavior but act as facilitators accelerating consumption processes. The implications highlight the importance of digital financial literacy and self-control in optimizing the benefits of e-wallets among students.